The use of aggregate from demolition rubble in the making of ordinary and structural concretes - Frick, Clayton (Department of Civil Engineering, 2016)
The aim of this thesis is to introduce the concept of recycling demolished concrete as aggregate which is then used in fresh concrete - to be known as "recycled concrete". Various aspects of concrete technology are covered and in this way recycled concrete is compared to conventional concrete. The work was performed in three phases, and it should serve as a guide to prospective users. Phase 1: Various recycled aggregates were tested according to standard specifications and were found to be satisfactory in most aspects. Recycled fine aggregate is very coarse though, and should be used with caution. The absorption and porosity of recycled aggregates should always be determined to enable their use in concrete. The specific gravity of such an aggregate should also be found to enable more accurate mix calculations. The highest compressive strengths normally possible for recycled concretes are between 56 and 71 MPa, but an average strength of 50 MPa should not be exceeded without thorough investigation, even though it is easily attainable. Phase 2: A wet-batching method of mix design was investigated and satisfactory recycled concretes were produced. Strength charts for such concretes are given. Methods of dry-batching are also presented, but are more complex than the wet-batch method. The water demand of recycled· fine aggregates was found to be considerably higher than for natural sands, and again the use of fine recycled aggregate should be carefully considered. Phase 3: The mechanical properties of recycled concretes were tested and Little difference found between recycled and conventional concretes. The compressive strengths were satisfactory and the elastic moduli sufficiently high, even though they were 15 to 20 percent Lower than those of corresponding dense concretes. The shrinkage of recycled concrete is comparable to that of conventional concrete, and the creep potential somewhat greater, although not excessivly so. The use of recycled coarse aggregate in both plain and structural concrete is then recommended as an alternative to the dwindling supply of natural aggregates. The use of recycled fine aggregate, however, is not recommended, although its use in Low-grade or mass concrete is condoned.